Breeding performance of Malawi Zebu cattle kept under traditional systems of management - Koning, R. de (Food and Agriculture Organization of the United Nations, 1977)
Reproductive performance of Malawi Zebu cattle were investigated. Reproduction record on breeding performance of 1500 cattle over a period of eight years were analysed. Discussions and data on age at first calving, distribution, interval, percentage and pattern of calving; variations in ovarian activity and relation between body weight and pregnancy rate;and breeding constraints included.